Abdominal Crises III (Res Medica, 2013)
The last of three articles written for Res Medica.Acute Inflammatory ConditionsWith the exception of the pancreas it is the hollow viscera which are involved in acute inflammatory disease. Always beginning as a localized process in the wall of the viscus the rapidity with which the inflammation spreads to the peritoneal space to produce peritonitis depends largely on the time taken for necrosis and perforation of the inflamed area to occur. It the reaction is slow, the inflamed area has often become adherent to adjacent structures or wrapped in omentum before perforation occurs so that even after this disaster the peritonitis remains localized for a further period and an abscess forms.